Municipal community centers as healthy settings: evaluation of a real-world health promotion intervention in Jerusalem - Deborah Barasche-Berdah; Sima Wetzler; Iva Greenshtein; Keren L. Greenberg; Elisheva Leiter; Milka Donchin; Donna R. Zwas (BMC, 2022)
Abstract Background This study presents an intervention designed to foster the implementation of health promotion programs within District Municipality Community Centers (DMCCs) in Jerusalem, and the creation of a peer network of healthy settings with a shared aspiration of collaborating and implementing health-promoting policies at the community level. We also present the evaluation strategy, based on the EQUIHP and RE-AIM frameworks. Methods Twenty DMCCs completed our program. This evaluation research involved a comprehensive seminar during the first year for DMCCs coordinators, teaching them the principles of health promotion. An educational kit was distributed during the second year. The evaluation strategy included a process evaluation and annual evaluations based on the EQUIHP and RE-AIM frameworks. The EQUIHP tool was divided into four dimensions of evaluation: 1) Framework of health promotion principles, 2) Project development and implementation, 3) Project management, and 4) Sustainability; while the RE-AIM domains included: 1)Reach, 2)Effectiveness, 3)Adoption, 4)Implementation and 5)Maintenance. Results The program led to high responsiveness among DMCCs and to the implementation of diverse health promotion initiatives, with a participation of approximately 29,191 residents. The EQUIHP evaluation showed an improvement in program quality in Year 2. The final RE-AIM evaluation presented a total median score of 0.61 for all domains, where 0 was non-performance and 1.0 was full performance. The 'Framework of health promotion principles' and 'Reach' components received the highest median score (0.83, 1.0 and 0.87), while the 'Sustainability and 'Maintenance' components received the lowest (0.5). Conclusions This innovative program adapts the Healthy Cities approach (initiated by the World Health Organization in 1986) to the development of community center health-promoting settings within the larger municipal framework, training local community center staff members to assess and address local health concerns and build community capacity. The local focus and efforts may help community actors to create health promotion programs more likely to be adopted, feasible in the 'real-world' and able to produce public health impact in the communities where people live. Moreover, collaboration and cooperation among DMCCs may lead to a broader community health vision, forging coalitions that can advocate more powerfully for health promotion. Trial registration NIH trial registration number: NCT04470960. Retrospectively registered on: 14/07/2020.